IMPLEMENTASI PEMBELAJARAN BAHASA ARAB MELALUI METODE YOUTUBE ARAB PODCAST DALAM PEMBELAJARAN MUFRODAT DI MTS MU’ALLIMAT MALANG - Umar Hamdan Zarkasyi; Mohammad Samsul Ulum; Faisol (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of Arabic language learning through the YouTube Arab Podcast method in vocabulary (mufrodat) instruction at MTs Mu’allimat Malang and to analyze its impact on students’ vocabulary mastery and self-confidence. The background of this research is based on the problem of students’ low confidence in actively using Arabic, which is influenced by fear of making mistakes and the lack of a supportive language environment (bi’ah lughawiyyah). This study employs a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques.The findings reveal that the use of YouTube Arab Podcast as a learning medium creates a more interactive and contextual learning atmosphere. Students are exposed to authentic language input through audio-visual content, which facilitates their understanding and acquisition of new vocabulary. Furthermore, this method contributes to the development of a more natural language environment, where students become accustomed to listening to and imitating Arabic expressions in daily contexts. Another significant impact is the improvement of students’ self-confidence in speaking, as they are provided with clear and engaging language models. Therefore, the implementation of the YouTube Arab Podcast method is proven to be effective in enhancing both vocabulary learning outcomes and students’ affective aspects.